INSENTIF PAJAK UNTUK CASH WAQF LINKED SUKUK (CWLS): PELUANG DAN TANTANGAN REGULASI: Studi Normatif tentang Harmonisasi Hukum Wakaf dan Perpajakan - Lulu Azkya Ramansyah; Misbah Khoirul Umam; Darul Saputro (STKIP Subang, 2025)
Cash Waqf Linked Sukuk (CWLS) is an innovative Islamic financial instrument that integrates cash waqf with state fiscal financing through sukuk issuance. This instrument has significant potential to support social financing and sustainable development. However, the optimization of CWLS still faces various challenges, particularly related to tax regulatory aspects. This study aims to analyze the opportunities and challenges of tax incentives in the implementation of CWLS in Indonesia. The research employs a normative juridical method using statutory and conceptual approaches, supported by a literature review of national journals and academic books published within the last five years. The findings indicate that cash waqf under the CWLS scheme has the potential to be treated as a deductible item from taxable income for waqif, while the sukuk returns allocated for social purposes require clearer tax treatment for nazhir. The main challenges identified include the absence of explicit technical tax regulations and the limited tax administrative capacity of nazhir institutions. This study recommends regulatory harmonization between waqf and taxation laws and the formulation of supportive fiscal policies to enhance the role of CWLS as an integrated Islamic social finance instrument in Indonesia.